抗リウマチ薬sulfasalazineはToll-like receptor 4刺激によるマクロファージからのHMGB1遊離を抑制することで炎症性疼痛を軽減する - 坪田, 真帆; 堂本, 莉紗; 関口, 富美子; 川畑, 篤史; 田村, ひなの; 西堀, 正洋 (日本薬理学会年会要旨集, 2022)
High mobility group box 1 (HMGB1), a nuclear protein, is released from various cells including macrophages (Mφ), and aggravates inflammation and pain. Given the involvement of HMGB1 and Toll-like receptor (TLR) 4 in the pathogenesis of rheumatoid arthritis (RA), we examined the effect of sulfasalazine (SSZ), an anti-RA agent, on TLR4-mediated inflammatory pain in mice, and on HMGB1 release from Mφ. The mechanical allodynia following intraplantar injection of lipopolysaccharide (LPS), a TLR4 agonist, was prevented by SSZ, an anti-HMGB1-neutralizing antibody, thrombomodulin alfa capable of inactivating HMGB1, ethyl pyruvate, an inhibitor of HMGB1 release from Mφ, or liposomal clodronate (Clo), a Mφ depletor, and by inhibitors of CaMK kinase, JAK or NF-κB. In Mφ-like RAW264.7 cells, the LPS-induced HMGB1 release was suppressed by SSZ, but not its metabolite, 5-aminosalicylic acid, and by inhibitors of JAK, CaMK kinase and NF-κB. SSZ suppressed the LPS-induced phosphorylation of STAT3 and CaMK4, but not NF-κB p65, in RAW264.7 cells. These results suggest that SSZ relieves inflammatory pain by reducing TLR4-dependent HMGB1 release from Mφ through inhibition of JAK/STAT and CaMK signals.